PENGELOLAAN BUDAYA SEKOLAH UNTUK MENINGKATKAN KARAKTER SISWA DI SMK NEGERI - Henni Isnani Selian; Muhammad Iqbal; Najmuddin Najmuddin (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This research aims: a) To describe school culture management planning to improve student character which is integrated into learning planning at SMKN 1 Kutacane. b) To find out the implementation of student character education. c) To find out about the supervision of character education at SMKN 1 Kutacane. This type of research uses a qualitative descriptive approach. The data sources in this research are primary data, namely the Principal, Deputy Principal, Subject Teachers, Guidance and Guidance Teachers, Extracurricular Advisors, Students and Administrative Staff. The techniques used in collecting data were observation, interviews and documentation. The data analysis used is data collection, data presentation, data reduction, and drawing conclusions. Research results: (1) The school principal formed a work team consisting of the Curriculum, Student Affairs, Religion Teachers and student coaches to create a character education plan. (2) Implementation is carried out in the classroom by integrating it into the subject under the guidance of the teacher and homeroom teacher. Implementation outside the classroom with student guidance and extracurricular coaches. (3) Supervision in class, making direct observations in the school environment. The evaluation is delivered at the end of the semester meeting, to determine the success of character education that has been implemented including: student character, facilities and infrastructure and financing